Umbilical vessel wall fatty acids after normal and retarded fetal growth. Issue 1 (January 1994) - Felton, C V; Chang, T C; Crook, D; Marsh, M; Robson, S C; Spencer, J A
Abstract : In a prospective observational study, the fatty acid content of human umbilical artery and vein wall phospholipids was determined in fetuses classified according to their change in abdominal circumference during the third trimester. Three groups were identified: appropriate for gestational age (AGA; 24 infants) and small for gestational age (SGA; 38 infants) with normal antenatal growth rate, and SGA with fetal growth retardation (22 infants). The venous linoleic acid (18:2 omega 6) content (expressed as a percentage of the total fatty acids identified) was greater in growth retarded SGA fetuses (3.5 (0.6)%) than in SGA fetuses with a normal growth rate (3.1 (0.5)%) and AGA fetuses (3.0 (0.5)%), whereas the venous contents of eicosatrienoic (20:3 omega 6) and docosahexaenoic acid (22:6 omega 3) were lower. In growth retarded SGA fetuses, the venous and arterial 20:3 omega 6 content correlated with the change in abdominal circumference. In SGA fetuses with a normal growth rate, lower contents of arterial 18:2 omega 6 and 22:6 omega 3 were associated with a smaller change in abdominal circumference and birth weight. Different metabolic derangements appear to underly normal and subnormal growth rate in SGA fetuses, suggesting that different strategies of dietary intervention may be required to aid fetal growth and reduce the sequelae of fetal growth retardation.